Administration of Probiotic sanolife Mic-S on Biological Performance of Vanamei Shrimp (Litopenaeus vannamei) PL 10 - Hasim, Hasim; Baidi, Nadia; Syamsuddin, Syamsuddin; Tuiyo, Rully (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
Vannamei shrimp is a fishery commodity that has important economic value for Indonesia. This is indicated by the increasing number and value of exports of this commodity. One of the efforts to encourage the production of vaname shrimp is through the use of probiotics. sanolife-MIC is a probiotic widely used in shrimp culture. The aim of the study was to analyze the feed profile and biological performance of Vaname PL 10 shrimp fed pellets with the Sanolife MIC-S probiotic capsule at different doses. The research method used is an experimental method using a completely randomized design (CRD) with four treatments (A: probiotic 0 gr/kg feed; B: probiotic 10 gr/kg feed; C: probiotic 12 gr/kg feed; D: probiotic 14 g/kg feed) and three replicates. What was tested in the study were probiotic profile tests, growth, feed efficiency and feed conversion. The data obtained were analyzed using ANOVA. The results showed that the feed profile that was encapsulated using sanolife MIC-S, the protein value, moisture content and ash content for the feed were shown by treatment B. The best fat content was treatment C. The best crude fiber content was treatment D. Weight growth rate, ratio The best feed conversion and feed efficiency was shown by treatment B, while the length growth and survival was indicated by treatment C.